Learning Strategies in Physical Education to Improve Physical Fitness: Systematic Literature Review - Adritya, Wenny; Mashud, Mashud (UNIVERSITAS NEGERI MAKASSAR, 2025)
Physical fitness plays a key role in supporting growth and fostering a healthy lifestyle among elementary students. However, physical education is often delivered using conventional methods that lack effectiveness in enhancing fitness levels. This study aims to identify learning models that effectively improve students' physical fitness. Using a Systematic Literature Review (SLR) with the PICO framework and PRISMA flow diagram, data were sourced via Publish or Perish from Google Scholar and Crossref. Keywords included “student physical fitness,” “physical education learning models,” and “teaching style in physical education.” From 1,000 initial articles, seven met the inclusion and exclusion criteria. Findings reveal that models such as Project-Based Learning (PjBL), circuit games, Puzzle Run, and play-based methods significantly enhance cardio-respiratory endurance, muscular strength, agility, and motor coordination. The study concludes that active, engaging, and contextual teaching approaches are more effective than conventional methods in improving students’ physical fitness.